Reflective Thinking in the Holy Qur’an: A Model Based on Cosmic Phenomena (The International Journal for Scientific Research, 2025)
This research summarizes the Holy Qur’an’s approach to thinking, highlights the importance of thought, and explores its universal manifestations and methods of development as presented in the Holy Qur’an. The descriptive methodology has been used in this research, as it is the most appropriate for the subject matter. The study concludes with several key findings, including:-      Reflective thinking is regarded as a profound act of worship through which individuals draw nearer to their Creator.-      The Holy Qur’an consistently praises those who engage in contemplation of the signs and creations of God.
Keywords: Reflective Thinking; Deliberation; Meditation